Úlceras por pressão submetidas à fotobiomodulação com diodo emissor de luz - Maria Emília de Abreu Chaves (2015)
Despite the advances in techniques for treatment of wounds, pressure ulcer is still a problem in all healthcare environments. This study aims to analyze the effects of a device light emitting diode (LED) in the treatment of pressure ulcers. The methodology is divided into two stages: the first is the device development and the second comprises the clinical trials. The developed device consists of a cluster of 60 LEDs (30 red and 30 infrared) arranged in circles. The clinical applicability of the device was tested in the Santa Casa Hospital in Belo Horizonte. Thirty participants with uninfected sacral pressure ulcers, aged 18 or over, both male and female were included and randomized to one of two treatment groups. The control group received daily conventional treatment, which consisted of a cleaning of the pressure ulcer with physiological saline followed by an alginate hydrogel dressing for a period of 4 weeks. Besides the daily conventional treatment, the experimental group received device applications, three times a week, totaling 12 sessions. The pressure ulcers were evaluated by area and temperature measurements. Based on the results, it can be affirmed that the application of LED device (630 and 940 nm) at a dose of 4 J/cm2 promoted a higher healing rate in pressure ulcers in the experimental group compared to the control; the temperature of pressure ulcers remained in the appropriate range for healing in both groups during the treatment sessions; there was a heating in the pressure ulcers immediately after the LED device application, but it was not significant. It can be concluded that the LED photobiomodulation protocol used in this study optimized the pressure ulcers healing and it is suggested as adjunctive therapy in the treatment of these wounds.